2018
DOI: 10.1177/1076029618770273
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-Induced Coagulopathy and Japanese Association for Acute Medicine DIC in Coagulopathic Patients with Decreased Antithrombin and Treated by Antithrombin

Abstract: Disseminated intravascular coagulation (DIC) in patients with sepsis represents a critical condition. Thus, a simple and rapid diagnosis is required. The purpose of this study was to compare the performances of a recently developed Sepsis-Induced Coagulopathy (SIC) with the Japanese Association for Acute Medicine (JAAM) DIC. Four hundred nine patients with sepsis having coagulopathy and antithrombin activity of less than 70% and treated with antithrombin were retrospectively analyzed, and the SIC and JAAM-DIC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 26 publications
2
26
3
2
Order By: Relevance
“…A comparison of the SIC and JAAM DIC criteria was also carried out, and the prevalence of patients with SIC was comparable to that of patients with JAAM DIC. The SIC criteria also showed similar performance for predicting the 28‐day mortality as the JAAM DIC criteria . Thus, the SIC criteria were suggested to identify a category similar to that identified by the JAAM DIC criteria.…”
Section: Future Perspectivesmentioning
confidence: 73%
“…A comparison of the SIC and JAAM DIC criteria was also carried out, and the prevalence of patients with SIC was comparable to that of patients with JAAM DIC. The SIC criteria also showed similar performance for predicting the 28‐day mortality as the JAAM DIC criteria . Thus, the SIC criteria were suggested to identify a category similar to that identified by the JAAM DIC criteria.…”
Section: Future Perspectivesmentioning
confidence: 73%
“…It was found that almost all patients with overt DIC also met criteria for SIC, and that SIC preceded overt DIC in every case. In another study, SIC criteria appeared to identify a patient group similar to that identified using JAAM DIC criteria . The result was interesting because in SIC criteria, FDP/D‐dimer adopted by JAAM DIC criteria was eliminated and SIRS score was replaced with SOFA score.…”
Section: Diagnosis Of Sepsis‐associated Dic and Sicmentioning
confidence: 99%
“…The usefulness of the SIC score has been validated . The ISTH DIC SSC members compared SIC and ISTH overt DIC scoring systems in sepsis patients with coagulopathy .…”
Section: Diagnosis Of Sepsis‐associated Dic and Sicmentioning
confidence: 99%
See 2 more Smart Citations